Etika Wahhabian dan Etika Protestan - Bahtiar, Riza (NALAR, 2017)
This paper effort to define the theology of Wahhabian which is divided into three, such as: tauhid rububiyah, tauhid asthma, and the nature and monotheism of worship, wahhabian ethos in general, followed by wahhabian ethics divided into five points, namely 1) "Takfir" over other Muslims as polytheists; 2) Return to the Quran and Hadith with the interpretation of zahirism; 3) Anti-intellectualism; 4). Political and military action is a religious act; 5) The blood and wealth of the enemy wahhabisme as profit, continued with parallel and ethical differences of Wahhabian with Protestant ethics.Keywords: Ethics, Wahhabian, Protestant